The politics of water reform and environmental sustainability in the Murray–Darling Basin. Issue 8 (17th November 2017) - Horne, James
ABSTRACT: This paper examines three actions by national and state governments – the role of the Cap, the Living Murray (TLM) and the National Action Plan for Water Security/Water for the Future, embodying the Murray–Darling Basin (MDB) Plan – in the Murray–Darling Basin over a 20-year period. The three actions sought to address declining environmental conditions through water policy reform. All were significant in their own way, but only the third offers the prospect of improving environmental outcomes. Taken together, the case studies illustrate that in real life and in complex, multilevelled policy-making, politics is central to water policy decision-making.